2005
DOI: 10.1007/s11882-005-0052-6
|View full text |Cite
|
Sign up to set email alerts
|

CD25+ T cells and regulation of allergen-induced responses

Abstract: CD4 T helper 2 (Th2) cells, with the characteristic interleukin (IL)-4, IL-5, and IL-13 cytokine secretion profile, play an important role in the initiation and perpetuation of allergic airways disease. It is clear from recent studies that CD4+ T cells with distinct cytokine-producing abilities have regulatory functions that limit allergic inflammation. Studies of allergic airway inflammation in mice have identified different types of T regulatory cells (Tregs) that control the disease phenotype. The cytokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 75 publications
(63 reference statements)
0
13
0
1
Order By: Relevance
“…Again, none of the studies were related to the topic of asthma, although Tregs have been shown to play an important role in moderating allergic asthma [54] and may be involved in the increased susceptibility of female mice for asthma [21].…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…Again, none of the studies were related to the topic of asthma, although Tregs have been shown to play an important role in moderating allergic asthma [54] and may be involved in the increased susceptibility of female mice for asthma [21].…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…Mice or humans with a deficiency of T reg cells, induced by antibody-mediated 1,2 or toxin-mediated 3,4 depletion or by mutations 5 and deletions 6,7 of the lineage specification factor Foxp3, manifest severe autoimmune disease. In addition to preventing autoimmunity, T reg cells can also suppress immune responses generated against tumor cells, 8,9 alloantigens, 10 allergens, [11][12][13] and microbial antigens. 14,15 Several mechanisms have been proposed to explain how T reg cellmediated suppression of effector immune responses occurs.…”
Section: Introductionmentioning
confidence: 99%
“…including infectious agents and allergens (Ostroukhova and Ray, 2005;Paust and Cantor, 2005;Suri-Payer and Fritzsching, 2006;Xystrakis et al, 2006;Zwar et al, 2006). They also suppress graft versus host disease and transplant rejection (Cohen and Boyer, 2006;Walsh et al, 2004).…”
mentioning
confidence: 99%